P96 Screening for cerebrovascular pathology on the basis of positive family history in the paediatric population. Issue 3 (14th February 2019) - Millward, CP; Tonder, LV; Foster, M; Williams, D; Griffiths, M; Kneen, R; Sinha, A; Mallucci, C
Abstract : Objectives: Neurovascular disorders are uncommon, complex conditions in children. We reviewed the screening practice and outcome of children referred to the neurovascular service on the basis of positive family history. Design: Retrospective review of prospectively maintained database. Subjects: Children referred to the neurovascular service on the basis of family history, for screening at our hospital. Methods: We retrospectively examined our database between July 2008 and April 2018 for the reasons for referral, family history, investigations performed, and the outcome of the screening process. Results: 44 children were reviewed (23 male, median age 10). Thirty-one children had an MRI/MRA brain. One child subsequently had uncomplicated digital subtraction angiography. Thirty children were referred due to a family history of subarachnoid haemorrhage, of which 17 had a single first-degree relative, and two had two first-degree relatives. Nine children were referred with a family history of arteriovenous malformation, (2 were associated with hereditary haemorrhagic telangiectasia). Five children were discussed due to a family history of non-specific haemorrhagic stroke. Seven children had a history of headache, (4 were prescribed Pizotifen for migraine). No neurovascular pathology was detected following screening within our cohort. Conclusions: A consensus screening policy does not exist but is required both to guide clinical practice and to assuage parental or patient concerns. We will survey UK paediatric centres to commence this process.